PENGARUH LATIHAN KNEE-TUCK JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI CLUB BOLA VOLI PUTRA IPLAI JUNIOR LUBUK PANDAN - Syafriadinata, Ridho; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study was conducted to determine whether there are effects of exercise on knee-tuck jump explosive leg muscle power in volleyball game so that when doing a smash to get maximum result. The design of this research is experimental, with a population of volleyball players of IPLAI Junior Lubuk Pandan, the data in this research is whole population with 11 people as the total. The instruments that used in this research is vertical jump test, which aims to measure the explosive power of leg muscles. Thereafter the data is processed statistically, to test the normality with lilifors test at significant level 0,05a. The hypothesis is the effect of knee-tuck jump exercise to explosive power of leg muscles. Based on analysis of T test, generates T count by 8.615 and amounted to 1.812. It means T table > T arithmetic. Based on the analysis of statistical data, the data is normal. Thus there is the effect of knee-tuck jump exercise towards explosive power of leg muscles in volleyball men’s IPLAI Junior Lubuk Pandan club.Keywords: Knee-Tuck Jump, Explosive Power of Leg Muscles.